2009
DOI: 10.1007/s00436-009-1328-x
|View full text |Cite
|
Sign up to set email alerts
|

Toltrazuril treatment of congenitally acquired Neospora caninum infection in newborn mice

Abstract: C57BL/6 mice were infected with Neospora caninum tachyzoites during pregnancy, yielding a transplacental infection of developing fetuses. Subsequently, congenitally infected newborn mice were treated either once or three times with toltrazuril (or placebo) at a concentration of 31.25 mg compound per kg body weight. Both toltrazuril and placebo treatment had no negative effect on newborns, as noninfected treated pups developed normally without differences in mortality and morbidity to matching nontreated contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 36 publications
1
11
0
2
Order By: Relevance
“…Toltrazuril and its metabolites have been shown in a number of studies to be effective against tachzyoites (Kritzner et al, 2002;Strohbusch et al, 2008). Using a similar approach to that of the present study with a murine model, Strohbusch et al (2009) demonstrated that the treatment of neonatal mice with toltrazuril reduced, but did not eliminate, the infection. Although not specifically stated, presumably both tachyzoites and bradyzoites would have been present in these treated neonatal mice.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Toltrazuril and its metabolites have been shown in a number of studies to be effective against tachzyoites (Kritzner et al, 2002;Strohbusch et al, 2008). Using a similar approach to that of the present study with a murine model, Strohbusch et al (2009) demonstrated that the treatment of neonatal mice with toltrazuril reduced, but did not eliminate, the infection. Although not specifically stated, presumably both tachyzoites and bradyzoites would have been present in these treated neonatal mice.…”
Section: Discussionsupporting
confidence: 67%
“…Toltrazuril, a symmetrical triazinone, is metabolized into ponazuril (toltrazuril sulfone). Both toltrazuril and ponazuril are effective against a broad spectrum of cyst-forming and non-cyst-forming apicomplexan protozoa (Haberkorn, 1996) including positive effects against N. caninum in vitro (Darius et al, 2004;Strohbusch et al, 2008) and in vivo, both in mice (Strohbusch et al, 2009) as well as in experimentally and naturally infected calves (Haerdi et al, 2006;Kritzner et al, 2002). However, in order for toltrazuril to reach its full effectiveness in clearing N. caninum infection, one study has shown that a supportive T cell-immune response is necessary (Ammann et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…However, interesting experimental studies that may result in an option for chemotherapeutic control at a later stage have been conducted. An effect of toltrazuril and its derivative ponazuril on tachyzoites on N. caninum has been shown in vitro and in vivo in calves (Strohbusch et al, 2009). In calves treated with ponazuril, the parasite was no longer detectable in the brain and other organs.…”
Section: Prevention and Controlmentioning
confidence: 97%
“…The calf may be chronically infected, with or without clinical symptoms (Anderson et al 2000;Dubey and Schares 2006) or Neospora free (Orozco et al 2012). Some experimental studies have investigated the importance of chemotherapeutic agents for the control of Neospora infections, such as toltrazuril and ponazuril (Kritzner et al 2002;Strohbusch et al 2009), monensin (VanLeeuwen et al 2010a, and a combination of sulphadiazine-trimethoprim and toltrazuril (Cuteri et al 2005).…”
mentioning
confidence: 99%